Reproductive Site Selection: Evidence of an Oviposition Cue in a Highly Adaptive Dipteran, Drosophila suzukii (Diptera: Drosophilidae). Issue 2 (24th January 2020) - Tait, Gabriella; Park, Kyoo; Nieri, Rachele; Crava, M Cristina; Mermer, Serhan; Clappa, Elena; Boyer, Gabriella; Dalton, Daniel T; Carlin, Silvia; Brewer, Linda; Walton, Vaughn M; Anfora, Gianfranco; et al.
Abstract: Drosophila suzukii (Matsumura) is a vinegar fly species that originates from Eastern Asia and has spread throughout Europe and the Americas since its initial detection in United States in 2008. Its relatively large, sclerotized, and serrated ovipositor enables the ability to penetrate ripening fruits, providing a protected environment for its egg and larval stages. Because the mechanism of oviposition site selection of D. suzukii is a matter of hypothesis, the aim of the present study was to elucidate behavioral and chemical aspects of short-range ovipositional site selection within the context of D. suzukii reproductive biology. The preference of D. suzukii to lay eggs on artificially pierced, previously infested, or intact fruits was tested. Video recordings and photographic evidence documented the release of an anal secretion over the fruit surface near the oviposition sites. Gas chromatographic analysis revealed the presence of 11 compounds detected only on the skin of egg-infested berries. Electroantennographic experiments with both sexes of D. suzukii highlighted the importance of six volatile compounds: methyl myristate, methyl palmitate, myristic acid, lauric acid, palmitic acid, and palmitoleic acid. Finally, a synthetic blend composed of the six compounds in a ratio similar to that found on the skin of egg-infested berries increased the oviposition rate of conspecific females. Data from our work suggest that the identified volatiles are cues for reproductive site selection. We discuss how these oviposition cues may affect the fitness of D. suzukii . The knowledge gained from this study may accelerate establishment of control strategies based on the interference and disruption of D. suzukii communication during the oviposition processes.